Periodic solutions of quasi-differential equations. (1996) - Boucherif, Abdelkader; García-Río, Eduardo; Nieto, Juan J.
Abstract : Existence principles and theorems are established for the nonlinear problem L u = f ( t, u ) where L u = − ( p u ′ ) ′ + h u is a quasi-differential operator and f is a Carathéodory function. We prove a maximum principle for the operator L and then we show the validity of the upper and lower solution method as well as the monotone iterative technique.